2015
DOI: 10.33073/pjm-2015-001
|View full text |Cite
|
Sign up to set email alerts
|

Virus Like Particles as Immunogens and Universal Nanocarriers

Abstract: A b s t r a c tOver the last two decades virus-like particles (VLPs) have become an important tool in biomedical research and medicine. VLPs are multiprotein structures that resemble viable virus particles in conformation but lack the viral genome. Consequently, they are non-infectious and non-replicative, but retain the ability to penetrate cells, making them useful for a vast spectrum of applications. Above all, VLPs mimicking genuine viruses in antigenic structure provide a safe alternative to attenuated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 105 publications
(69 reference statements)
0
53
0
Order By: Relevance
“…Although synthetically prepared nanoparticles have yet to show the level of ordered antigen arrangement found on viruses and virus-like particles derived from cell culture systems [181,182], ongoing studies continue to demonstrate emerging techniques to couple antigens of interest to nanocarriers. In the last section of the review, we review commonly used methods for coupling antigens with nanoparticles.…”
Section: Repetitive Antigen Display For Immune Activationmentioning
confidence: 99%
“…Although synthetically prepared nanoparticles have yet to show the level of ordered antigen arrangement found on viruses and virus-like particles derived from cell culture systems [181,182], ongoing studies continue to demonstrate emerging techniques to couple antigens of interest to nanocarriers. In the last section of the review, we review commonly used methods for coupling antigens with nanoparticles.…”
Section: Repetitive Antigen Display For Immune Activationmentioning
confidence: 99%
“…Devoid of viral genetic material, VLPs do not replicate within the host cell, but can be used as carriers for nucleic acids, proteins or drugs. Numerous studies have demonstrated that VLPs originating from different viral species may be produced using eukaryotic expression systems (reviewed in [1][2][3]). Coronaviruses-enveloped, positive-stranded RNA viruses that cause common respiratory diseases in humans and a broad variety of diseases in animals are also able to form such structures.…”
Section: Introductionmentioning
confidence: 99%
“…VLPs can stimulate robust humoral and cellular immunity responses via several mechanisms, including mimicking the structure and conformation of the native virus, possessing repetitive elements, and larger dimensions [12][13][14]. Given these unique characteristics, VLPs became interesting in vaccine design and development, employed as platforms presenting exogenous 4 antigens [13,15] and as carriers to deliver nucleic acids, drugs, and proteins [16].…”
Section: Introductionmentioning
confidence: 99%